A Scientometric Analysis of Global Synthetic Biology Literature - KT, Naheem (Qualitative and Quantitative Methods in Libraries, 2022)
The current study provides a scientometric overview of the global Synthetic Biology literature from 2005 to 2019. Data for the analysis were obtained from the Web of Science Core Collection database of Clarivate Analytics. The results showed that the global Synthetic Biology literature consisted of 12012 publications during 2005-2019. Based on the data analysis, it is observed that the publications on synthetic biology show an increasing trend during recent years. It annually increased from 202 to 1534 from the year 2005 to the year 2019, with an annual average growth rate of 16.17 per cent. The global publication output in Synthetic Biology registered an average citation per publication rate of 27.44 from 2005 to 2019. The geographical distribution of output indicates that 96 countries contributed to the total 12012 publications during this period. Authors from countries like the USA, U.K., and China contributed a significant share of publications. Massachusetts Institute of Technology, USA, was found the most productive institution with 348 publications. Fussenegger M of Swiss Federal Institutes of Technology (ETH), Switzerland, was the most prolific author.